Assessment of Patient Satisfaction from Nursing Care in Hospitals of Iran University of Medical Sciences - S Joolaee; F Hajibabaee; E Jafar Jalal; N Bahrani (Tehran University of Medical Sciences, 2011)
Background & Aim: Patient satisfaction has been recognized as a key indicator of health care quality which is used by accreditation agencies to monitor quality of care in hospitals. A high proportion of health caregivers are nurses. The services provided by nurses are significantly influential in satisfaction of patients. The aim of this study was to assess patients' satisfaction from nursing care in hospitals of Iran University of Medical Sciences in 2010. Methods & Materials: In this cross-sectional study, we recruited 200 patients from different wards (except for special wards, Emergency department, Pediatric and Psychiatric wards) at the time of discharge from hospital through multistage sampling method. Data were collected using Patient Satisfaction Instrument (PSI). Data analysis was performed using descriptive statistics, chi-square and regression analysis. Results: Majority of patients (72%) were moderately satisfied. Patient satisfaction had a significant relationship with the type of ward (P≤0.001), and type of hospital (P≤0.001). Of demographic variables, only patients' level of education was significantly associated with patient satisfaction (P≤0.019). Conclusion: In this study, patients were moderately satisfied from nursing care services. Educating hospital staff, especially nurses; and encouraging them to actively participate in activities to promote patient satisfaction should be a priority for hospital management. We should also consider that in a competitive market of health and treatment care giving, institutions that put patient satisfaction as their main goal are more successful.   Key words: patient satisfaction, nursing care services, hospital